Markers of distress among behavioral and physical health evacuees prior to emergency departure from Antarctica. (January 2023) - Kim, Jinu; Cifre, Anthony; Bower, Joanne; Connaboy, Christopher; Simpson, Richard; Alfano, Candice
Abstract: Although incidences of psychological crises occurring during space flight are reportedly rare, such events remain a distinct possibility and potential threat to future long-duration missions (e.g., a Mars mission). Extended residence in Antarctica offers an ideal setting for examining high-risk profiles for psychological crises. We therefore utilized data from a nine-month longitudinal study conducted at the McMurdo station to examine baseline and monthly reports of psychological and physical symptoms among four emergency evacuees compared to the remaining McMurdo sample ( n  = 84). Emergency evacuation occurred for medical reasons ( n  = 2) or for psychiatric reasons ( n  = 2). Evacuees were White, between 29 and 47 years of age, and mostly male ( n  = 1 female). There were few differences in evacuees' baseline scores compared to the full sample. Monthly assessments showed elevated anxiety symptoms to be most common among all evacuees. Elevated physical symptoms were also apparent among a psychiatric and a medical evacuee in the months prior to evacuation. For one psychiatric evacuee, declines in positive emotions preceded increased problems with self-regulation before evacuation. While preliminary, findings contribute to sparse information about the symptoms that precede emergency evacuations from extreme environments and underscore the importance of regular, structured self-report assessments. Highlights: Description of symptoms associated with emergency evacuation from Antarctica is limited. We examined monthly changes in mental and physical health symptoms among four evacuees. Anxiety was the most common and severe symptom reported by medical and psychiatric evacuees. Increased physical complaints were endorsed by two evacuees during the month prior to evacuation. Ongoing assessment of these domains is recommended in extreme environments.